Adsorption Properties of Mixed Surfactant for Nonyl phenol Ethoxylate and Dehyquarte E-CA in Aqueous System at Liquid – Air Interface - H. Kareem, Sameer (Iraqi Journal of Science, 2023)
The micellization for an aqueous binary mixed system of Nonyl Phenol Ethoxylate ( NPE ) and Dehyquarte E-CA (DE-CA) were studied by means of surface tension measurement. The surface tension was measured for the solutions of the single and five mixed systems at 25ᵒC in order to determine critical micellization concentrations (CMC), surface excesses (Γ), and the surface area occupied by a molecule (Am) as a function of mole fraction of (NPE). The CMC,s values obtained decrease with increasing mole fraction of NPE in the mixture, and the synergism was observed at 0.9 mole fraction. Based on the regular solution theory, the compositions of the micellar phase (X1m) and the interaction parameter in micelles (βm) were calculated, and the result obtained at a low mole fraction indicates a mutual electrostatic repulsion between the surfactant molecules in the micelles, but at high mole fraction an attraction have been observed. The synergism in surface tension reduction was examined by minimum surface free energy ( ). The CMC-X2 curve showed a negative deviation from ideal mixing.